Rio que esquece onde nasce, seca e morre: educação para as relações étnico-raciais no Programa Curumim do Sesc São Paulo - Santos, Patricia Janaina (2025)
Since the enactment of Law 10.639/03, reflections on education for ethnic-racial relations have occupied a significant space in educational discussions over the past twenty years. The field of non-formal education, in its various areas of practice, has developed educational practices that build knowledge and learning about cultural diversity and racial relations among children. The research primarily aims to analyze the cultural-educational actions of the educators’ teams in the Curumim Program of Sesc São Paulo, situating and reflecting on how these actions contribute to and enable education for ethnic-racial relations from childhood. The research is characterized by a qualitative approach (Creswell, 2014; Chizzotti, 2006, 2018), based on descriptive-interpretative, using bibliographic research, analysis of Curumim Program documents, and face-to-face interviews using a semi-structured script applied to educators and reference technicians. Among the theorists supporting the foundational concepts of this research are the contributions of Nilma Lino Gomes (2001, 2002, 2007, 2023); Petronilha Beatriz Gonçalves e Silva (2007, 2013); Eliane Cavalleiro (2001, 2023) about black childhoods, racism, and ethnic-racial relations. Anete Abramowicz and Tatiane Rodrigues (2010); Anete Abramowicz and Fabiana de Oliveira (2010); Anete Abramowicz and Ana Cruz (2015); Renato Nogueira (2019a, 2019b, 2020); Luiz Rufino (2019, 2021) addressing the implications of diversity, interculturality, and the production of difference in education; Gimeno Sacristán (1995, 2013); Nilma Lino Gomes (2007, 2012, 2019) e Miguel Arroyo (2011, 2014), who constitute the theoretical bases of curriculum studies; and Maria da Glória Gohn (2007, 2010, 2015); Jaume Trilla (2008) and Valeria Aroeira Garcia (2009), authors contributing to the discussion of non-formal education. The results of the analysis highlight the construction of a significant field of cultural-educational practices and actions that have contributed to the appreciation of Black cultures and leadership, the construction of identity, and the racial belonging of the participating children